Investigation on Wear Resistance of Coated Cutting Tools Based on 17-4PH Stainless Steel Cutting Tests - Liu, Zhanfeng; Wang, Zhe (Asian Journal of Chemistry, 2014)
Based on the theoretical study of cutting tool wear and the systematic analysis of the parameters affecting the wear resistance of the tools, this paper presents an investigation on the effect of coating layers on the wear resistance of cutting tool inserts. In this project, four coated cutting tool inserts were selected for the 17-4PH stainless steel cutting tests and the wear morphology and life span of the tools were studied by a scanning electron microscope (SEM) and energy spectrum analysis. According to the results, the TiAIN coating layer by the physical vapor deposition coating process displays optimal thermal stability, high resistance to oxidation even at elevated temperatures and superior durability with difficult-to-cut materials. Conversely, the other three samples exhibited relatively poor performance due to the differences in composition and structure of the coating layers.